67 The occurrence of contaminated blood culture in paediatric unit in DGH, simple intervention to prevent cost and unnecessary treatment. (17th August 2022) - Sanchez, Violeta Torres; Mohamed, Amel; Vardhan, Madhur
Abstract : Aims: Micro-organisms are present on the skin surface of patients, staff and the immediate patient environment which can result in contamination of blood cultures. Contamination can lead to inappropriate treatment, prolonged hospital stay, increased cost (estimated: £5000/contaminated culture), family and patient inconvenience and it affect mandatory surveillance data and protocols. The aim of this audit is to assess the occurrence of contaminated blood cultures over a 4 month period in the paediatrics department of a DGH, to identify any areas for improvement and recommend interventions to decrease contamination. This will be achieved by emphasising the importance of ANTT (Aseptic Non-Touch Technique) and by creating a blood culture pack as a quality improvement project. The blood culture pack will include all the required equipment to facilitate correct ANTT and a procedure sticker will be added to the microbiology form to prompt the individual taking the blood culture to apply ANTT and complete the required documentation upon taking a blood culture. Methods: A retrospective review of the electronic health records of paediatric patients, who had a positive blood culture over a 4 month period then identify those with pathogens who are most likely contamination – related. Results compared against key performance indicator of blood culture contamination in adult of <3%) Results: Total number of blood culture done in this period was 306, 15 (4.9%) cultures were positive of which 3% (n=9) were identified as contaminated based on the pathogen isolated. Risk factors identified were the location in the hospital where blood culture was taken with cultures coming from the postnatal ward being the most likely to have contaminated culture ( n=5 (1.7%); followed by blood cultures in paediatric A&E and paediatric ward (n=4(1.3%). Main challenges identified were lack of universal approach to the procedure of taking blood culture and difficulty identifying the location and the person responsible for the procedure. Conclusion: Contaminated blood culture leads to prolonged hospital stay and increased cost. Simple intervention can improve ANTT practice and ensure universal approach and complete documentation. Re-audit is required to measure the effect of these interventions on the occurrence of contaminated blood culture.